An Ordinance to Regulate the Carrying of Concealed Weapons and to Prohibit the Carrying of the Same Except as Herein Provided, in Montclair Times, May 15, 1897, at 8 - (:unkn) unknown (My University, 1897)
No person shall carry any deadly weapon concealed on his person within the Town of Montclair except members of the police force of the Town of Montclair, public officers either of the United States or of this State or any sub-division thereof who are duly authorized by law to carry such weapons and persons to whom permits shall have been issued as hereinafter provided.
Keywords: CARRY - CONCEALED